Growth and Yield of Her (Ziziphus mauritiana Lamk) cv. Seo Under Different Pruning Severities - Mukherjee, S; Soni, A K (Annals of Arid Zone, 2016)
Effect of different pruning severities were studied on the performance of ber(Ziziphus mauritialla Lamk.) CV. Seo for 2 consecutive years. The treatments consisted of five pruning severities namely; no pruning (control), pruning upto 4th, 6th and 8th secondaries and also at 90 em or 3/4th length of the shoot. The weighl of pruned wood. plant height, plant spread, stock and scion girth. number of primary buds upto which secondary branches were arising annual shoot growth, per cent fruit set and fruit drop and yield differed significantly with various pruning severities. The maximum yield (61.82 kg) was obtained from trees which were pruned upto 6th secondaries.